Reducing child mortality in India in the new millennium - Mariam Claeson; Eduard R. Bos; Tazim Mawji; Indra Pathmanathan (Bulletin of the World Health Organization, 2000)
Globally, child mortality rates have been halved over the last few decades, a developmental success story. Nevertheless, progress has been uneven and in recent years mortality rates have increased in some countries. The present study documents the slowing decline in infant mortality rates in India; a departure from the longer-term trends. The major causes of childhood mortality are also reviewed and strategic options for the different states of India are proposed that take into account current mortality rates and the level of progress in individual states. The slowing decline in childhood mortality rates in India calls for new approaches that go beyond disease-, programme- and sector-specific approaches.